Natural Fibers, Bio- and Nanocomposites - Kalia, Susheel; Avérous, Luc; Njuguna, James A. K.; Cherian, Bibin Mathew; Dufresne, Alain (Cranfield University, 2011)
The field of bio- and nano- polymer composite materials for advanced structural and medical applications is a fast emergent area and subject of scientific attention. Natural fibers have received great interest as fillers for polymer composites because of the environmental issues in combination with their low cost. Cellulose nanofibers reinforced polymer composites is a fast growing area of research because of their enhanced mechanical, thermal and biodegradation properties. Composites with polymer matrices and cellulose nanofibers are increasingly regarded as an alternative to conventional composites. The properties of nanocomposite materials depend not only on the properties of their individual constituents but also on their morphology and interfacial characteristics. This rapidly expanding field is generating many exciting new materials with novel properties. The special issue will be interesting for researchers working in this field as it will deals with cellulose fibers, nanofibers and covers the latest advances in bio- and nano- polymer composite materials.